Zinc-Altered Immune function - Ibs, Klaus-Helge; Rink, Lothar (The Journal of nutrition, 2003)
Zinc is known to be essential for all highly proliferating cells in the human body, especially the immune system. A variety of in vivo and in vitro effects of zinc on immune cells mainly depend on the zinc concentration. All kinds of immune cells show decreased function after zinc depletion. In monocytes, all functions are impaired, whereas in natural killer cells, cytotoxicity is decreased, and in neutrophil granulocytes, phagocytosis is reduced. The normal functions of T cells are impaired, but autoreactivity and alloreactivity are increased. B cells undergo apoptosis. Impaired immune functions due to zinc deficiency are shown to be reversed by an adequate zinc supplementation, which must be adapted to the actual requirements of the patient. High dosages of zinc evoke negative effects on immune cells and show alterations that are similar to those observed with zinc deficiency. Furthermore, when peripheral blood mononuclear cells are incubated with zinc in vitro, the release of cytokines such as interleukins (IL)-1 and -6, tumor necrosis factor-α, soluble IL-2R and interferon-γ is induced. In a concentration of 100 μmol/L, zinc suppresses natural killer cell killing and T-cell functions whereas monocytes are activated directly, and in a concentration of 500 μmol/L, zinc evokes a direct chemotactic activation of neutrophil granulocytes. All of these effects are discussed in this short overview.